Branding Innovation in Pesantren: The Role of Students Improving Image and Public Trust - A'yuni, Jurotul (Jurnal Pendidikan Nusantara, 2024)
The research was carried out at the Darul Fikri Islamic Boarding School educational institution to find out how the educational institutions at the Islamic boarding school are. This type of research is qualitative and uses ethnography. Techniques for collecting data at Darul Fikri Islamic Boarding School educational institutions using interview methods and direct field observations. The results of this research are to find out the efforts made by students in branding a school education institution and what impact it has after students carry out Branding of educational institutions in schools. The efforts made by students are to study seriously and develop all the potentials possessed by students. Students must synergize in the policies that have been established by educational institutions at the Darul Fikri Islamic Boarding School. The activities of students in comparing educational institutions are as follows: social service as a means of introducing institutions, students participating in competitions held outside of school, involving majlis table outside and inside the school as a place for class XII final exams and so forth.